Scalable, low-cost, and environment-friendly preparation of high strength carbon-matrix composites with tree-root-like structured reinforcements. (June 2022) - Chen, Qichen; Yang, Zefeng; Lin, Jiahui; Wei, Wenfu; Li, Hao; Yin, Guofeng; Liu, Yijie; Li, Pengli; Tu, Chuanjun; Gao, Guoqiang; Huang, Xingyi; Wu, Guangning
Abstract: The poor interfacial interaction between carbon fiber (CF) and a matrix is the main factor restricting the enhancement in performance of carbon-matrix composites. Herein, CF was modified via a facile high-speed blending with matrix pitch-cokes particles. AFM force measurements and 3D particle tracking simulations unlocked the blending CF@pitch-cokes assembly mechanism. Inspired by the strong interaction between tree roots and soil, a tree-root-like reinforced structure was designed and developed in carbon-matrix composites by the subsequent carbonization coupling effect between the pitch-cokes adsorbed CF surface and the carbonized matrix. It was found that the tree-root-like structure significantly improved the interfacial interaction and enhanced the mechanical properties of the carbon-matrix composites. Compared with the pristine CF reinforced composites, the compressive strength (158.33 ± 1.95 MPa) and flexural strength (36.65 ± 1.32 MPa) of the carbon-matrix composites with tree-root-like structures increased by 101.4% and 65.8%, respectively. A mechanical interlock mechanism is suggested to explain the enhanced mechanical properties of the composites. This work provides a facile strategy for improving the interface of CF-reinforced carbon-matrix composites and paves the way for scalable, low-cost, and environment-friendly processing of high strength composites. Graphical abstract: Image 1 Highlights: A carbon fiber (CF) reinforced carbon-matrix composite material with tree-root-like structure designs is fabricated. The surface design through facile high-speed blending with matrix pitch-cokes particles can modify CF greatly. The blending CF@pitch-cokes assembly mechanism stems from adhesion and electrostatic forces. The preparation efficiency of composites can be enhanced through the scalable, low-cost, and environment-friendly method.